1987
DOI: 10.1002/1097-0142(19870815)60:4<827::aid-cncr2820600419>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy study of 1206 acute and chronic leukemias (1958 to 1982)

Abstract: Autopsy data on 1,206 children and adult patients with acute myelocytic leukemia (AML) (585), chronic granulocytic leukemia (CGL) (204), acute lymphocytic leukemia (ALL) (308), and chronic lymphocytic leukemia (CLL) (109) obtained from 1958 to 1982 were reviewed. This analysis has shown that, whereas the proportion of patients with residual AML at any anatomic site decreased significantly and uniformly over the entire study period, significant corresponding decreases in patients with CGL and ALL occurred only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
1
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(143 citation statements)
references
References 27 publications
8
130
1
4
Order By: Relevance
“…In autopsy studies of patients with NHL, disease in the uterus was found in approximately 0.5% (17)(18)(19). The uterus is affected more commonly by chronic lymphocytic leukemia: 7.1 to 14.0% of patients have had uterine involvement (18,20). Because of its infrequent nature, NHL involving the uterus may present diagnostic difficulties for pathologists who are unfamiliar with the clinicopathologic characteristics of the disease in this location.…”
Section: Discussionmentioning
confidence: 99%
“…In autopsy studies of patients with NHL, disease in the uterus was found in approximately 0.5% (17)(18)(19). The uterus is affected more commonly by chronic lymphocytic leukemia: 7.1 to 14.0% of patients have had uterine involvement (18,20). Because of its infrequent nature, NHL involving the uterus may present diagnostic difficulties for pathologists who are unfamiliar with the clinicopathologic characteristics of the disease in this location.…”
Section: Discussionmentioning
confidence: 99%
“…The extra medullary relapse could be due to poor penetration of chemotherapy at anatomic sites of leukemic proliferation [9].…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of a large autopsy series by Barcos et al 2 showing an incidental finding of CLL infiltration of the CNS in 20% of cadavers, cases of CNS involvement in B-cell CLL have rarely been reported. The majority of established cases include leptomeningeal spread and spinal cord involvement.…”
Section: Chronic Lymphocytic Leukemia Infiltration Of the Pituitary Gmentioning
confidence: 99%
“…In 2001, Rye et al 25 reported postmortem histological findings of CLL infiltration of the pituitary gland extending into the posterior pituitary stalk in a 61-year-old man with known CLL who died of complications of hyponatremia and lower respiratory tract infection. According to Barcos et al, 2 CLL infiltration of the pituitary gland associated with apoplexy had not been reported previously, although Kingdon et al 15 described a case of pituitary apoplexy in a patient with a pituitary abscess secondary to hypogammaglobulinemia from known CLL. The histopathology revealed squamous tissue and inflammatory changes consistent with an abscess with no evidence of direct CLL involvement.…”
Section: Chronic Lymphocytic Leukemia Infiltration Of the Pituitary Gmentioning
confidence: 99%